Parenting self-efficacy on autism spectrum disorder context: a literature review - Costa e Silva, Mariana; Roama-Alves, Rauni Jandé (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
Autism spectrum disorder (ASD) is a disease whose diagnostic characteristics require a significant change in daily life and family dynamics. Incorporating parents or caregivers into the treatment and ensuring their well-being becomes important for the development of the person with ASD. A construct that is associated with these issues is parental self-efficacy. Thus, the objective of the recent study is to identify studies with the topic "parental self-efficacy in the context of ASD" and the psychometric instruments used and characterise them. To this end, a bibliographic review was carried out with studies indexed in PubMed, PsycINFO, Web of Sciences and CAPES Magazines that addressed the topic and used a psychometric instrument to evaluate self-efficacy. Bibliometric analysis of the data and thematic categorical content analysis were carried out. The results point to three thematic foci in the analysis of parental self-efficacy in the context of ASD with constructs related to parental cognition as the main variables. Most of the instruments used for evaluation are related to parental self-efficacy in the general context, with only two specific instruments identified for ASD. The need to carry out more studies in the area and to have specific instruments for ASD is emphasised.